THE ASSOCIATION «COMMONWEALTH OF EDUCATIONAL ORGANIZATIONS NAMED AFTER A.S. PUSHKIN AND TEACHERS» AS A RESPONSE TO THE SOCIOCULTURAL TRANSFORMATION IN EDUCATION - Shagaeva, A (Uzbekistan Open Conference, 2025)
The article examines the example of the activities of the international Association «Commonwealth of Educational Organizations named after A.S. Pushkin and Teachers» as a practical model of response to the crisis of identity of traditional educational institutions. The study focuses on the concept of a methodological system for developing a spiritual and moral personality in the modern educational paradigm of Pushkin's Pedagogy as a value-based and activity-oriented system that allows for the preservation of the cultural code and ensures a dialogue of cultures in the context of globalization.
Keywords: sociocultural transformation; spiritual and moral values; dialogue of cultures; network society; cultural heritage; methodological system; unified educational environment; international cooperation